The role of academic leaders in activating the social participation in the Imam Abdulrahman Bin Faisal University - Al-Ghunaim, Esra'a Jassim Hamad; Bani Mortada, Ahmed Suleiman Mohammed (Journal of Educational and Psychological Sciences, 2019)
This study aims to uncover the role of academic leaders in activating the social participation in the Imam Abdulrahman Bin Faisal University and is conducted from the student's point of view and to identify the significance of differences according to varying criteria (gender, academic track, and the level of study.(To achieve this, the researcher used the descriptive, analytical approach and constructed the questionnaire as a data collection tool. The questionnaire was composed of (50) items covering five domains: (Partnerships with families, Community service, Community resource development, Volunteering, Public relations and communication within communities). The study involved the entire student population consisting of both male and female students attending the Imam Abdulrahman Bin Faisal University. Of approximately (36,820) students, a random sample of (1841) students was generated and represent 5%, and the data was processed statistically by SPSS.The study reached several results, the most significant of which are:• Members of the sample study rated the role of academic leaders in activating community participation with a low level in all fields of study.2.There are statistically significant differences between the views of the sample study in all areas due to gender variables favoring females. There are also differences according to the academic track which favors the scientific colleges.In light of the results, the researcher advises the following recommendations:- Initiate organizing field visits by students to schools, companies, associations and medical centers. Arranging tours to the directors of some companies and institutions of the university may play a vital role in supporting different disciplines respective to their nature.- Issue regulations for voluntary community work at the university supported by a list of cooperating and related authorities, incentives, violations, and penalties.
Keywords: Academic Leaders; Community Participation; Imam Abdulrahman Bin Faisal University